Exergy analysis of supersonic steam jet condensed into subcooled water. (April 2020) - Li, Wenjun; Miao, Lili
Highlights: Exergy analysis model of supersonic steam jet condensed into subcooled water was developed. Effects of physical and geometric parameters on exergy transfer and transition were investigated. Damping-energy properties of supersonic steam jet were investigated. Abstract: Exergy analysis of supersonic steam jet condensed into subcooled water was conducted via a numerical method. A thermal phase-change model was employed by Ansys, and considering turbulence interaction and turbulent dispersion force, three-dimensional simulations were conducted to simulate supersonic steam jet at different test conditions. Results indicated that the exergy flow of steam jet was mainly affected by water temperature and inlet steam pressure. The total physical exergy flow decayed monotonically due to the significant irreversible losses caused by heat and momentum transfer. For under-expanded supersonic steam jet, the peak distributions of steam kinetic exergy flow were obtained. The peak distributions of the water enthalpy exergy flow were also obtained at low water temperatures (293.15 K and 303.15 K). In addition, water temperature was found to be the main factor in the damping-energy properties of the supersonic steam jet. The damping-energy ratio and decay rate of the time-averaged kinetic energy decreased with the increase in water temperature, and a correlation was proposed to predict the time-averaged kinetic energy decay ratio.